Integrating the prevention and control of rheumatic heart disease into country health systems: a systematic review protocol. Issue 6 (22nd June 2019) - Abrams, Jessica; Watkins, David; Abdullahi, Leila H; Engel, Mark E; Zuhlke, Liesl J
Abstract : Introduction: Rheumatic heart disease (RHD) is a preventable chronic condition affecting the valves of the heart. RHD prevention and care programmes have historically originated in more developed countries, implemented in a targeted (or vertical) manner and evaluated using non-controlled approaches. Taking a broad view of the integration of RHD activities within the whole system is critical for health planning in low-income regions with a high burden of RHD and less robust health systems. Therefore, we propose to conduct a systematic review to assess RHD programme models in order to gain a better understanding of the extent of integration within relevant health systems. Methods and analysis: A predefined search strategy will be used to search for relevant articles published in English from January 1990 to December 2017. Electronic databases PubMed, Scopus, Web of Science, Africa Wide, CINAHL, Cochrane Central Register of Controlled Trials, Google Scholar and Global Index Medicus will be searched, as well as reference lists of relevant articles published. A standardised data extraction form will be used to obtain information for analysis from the included studies. The quality, reliability and risk of bias of included studies will be assessed using design-specific criteria. Programme integration will be analysed according to stewardship and governance, financing, planning, service delivery, monitoring and evaluation, and demand generation. Programme inputs, outputs and impact will also be described. Ethics and dissemination: No ethical approval is required. Findings will be disseminated in a peer-review journal in accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses guidelines. PROSPERO registration number: CRD42017076307